2019
DOI: 10.1111/jebm.12368
|View full text |Cite
|
Sign up to set email alerts
|

Periostin as a novel biomarker of cardiovascular disease: A systematic evidence landscape of preclinical and clinical studies

Abstract: Background Periostin is a matricellular protein, expressed in various normal adult and fetal tissues. Recently, elevated periostin levels have been reported in heart failure, coronary artery disease, and stroke. However, there is lack of clinical studies to clarify the prognostic significance of systemic periostin levels in cardiovascular diseases (CVDs). The aim of the study was to perform a systematic review of published evidence on periostin and CVDs, and to clarify the diagnostic and prognostic significanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 45 publications
0
15
2
Order By: Relevance
“…Furthermore, in a study conducted by Chen et al (2017), it was shown that in neonatal mice, the Pn level was significantly increased at 1, 3 and 7 days after an ACS (p < 0.01) [39]. Recent data also proved that Pn is involved in the atherosclerosis process and its serum level is increased in advanced forms of heart failure or ACS [40].…”
Section: Inflammatory Biomarkers In Cardiovascular Disease and Periodontal Diseasementioning
confidence: 95%
“…Furthermore, in a study conducted by Chen et al (2017), it was shown that in neonatal mice, the Pn level was significantly increased at 1, 3 and 7 days after an ACS (p < 0.01) [39]. Recent data also proved that Pn is involved in the atherosclerosis process and its serum level is increased in advanced forms of heart failure or ACS [40].…”
Section: Inflammatory Biomarkers In Cardiovascular Disease and Periodontal Diseasementioning
confidence: 95%
“…Post-percutaneous coronary intervention (PCI) patients represent a special CVD population (2), as they require secondary prevention for coronary heart disease (3). Predicting further CVD risk in such populations is critically relevant for clinical decision making, and novel factors that are potentially associated with CVD risk are being investigated (4). Lipid profiles are the most critical factors for CVD prevention, and low-density lipoprotein cholesterol (LDL-C) is a key risk factor for CVD (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…9 Altered and overexpression of periostin was found in wide variety of diseases including cancer, lung disease, and CVD. 8,10 Periostin may critically act as a scaffold and remodeling protein in inflammatory responses, obesity, and insulin resistance, that may reflect a novel molecular hint for the pathogenesis of T2DM and obesity. 11 As TG have risen as the favored storage supplement for buffering against variations in energy demand and accessibility, dysregulated TG collection is firmly related to chronic inflammation, obesity and metabolic disorder.…”
Section: Introductionmentioning
confidence: 99%